The functions of the cytoskeleton and associated proteins during mitosis and cytokinesis in plant cells - Li, Shanwei; Sun, Tiantian; Ren, Haiyun (Frontiers in Plant Science, 2015)
In higher plants, microtubule-based and actin filament-based structures play important roles in mitosis and cytokinesis. Besides the mitotic spindle, the evolution of a band comprising cortical microtubules and actin filaments, namely, the preprophase band, is evident in plant cells. This band forecasts a specific division plane before the initiation of mitosis. During cytokinesis, another plant-specific cytoskeletal structure called the phragmoplast guides vesicles in the creation of a new cell wall. In addition, a number of cytoskeleton-associated proteins are reportedly involved in the formation and function of the preprophase band, mitotic spindle, and phragmoplast. This review summarizes current knowledge on the cytoskeleton-associated proteins that mediate the cytoskeletal arrays during mitosis and cytokinesis in plant cells and discusses the interaction between microtubules and actin filaments involved in mitosis and cytokinesis.